2019
DOI: 10.3748/wjg.v25.i15.1817
|View full text |Cite
|
Sign up to set email alerts
|

Considerations of elderly factors to manage the complication of liver cirrhosis in elderly patients

Abstract: The aging of the organ function causes sensitivity to the disease progression and need careful consideration for the medical treatment. With the increase of aging population, the opportunity to provide medical treatment for people in very old age is rapidly increasing therefore, the understanding of the various physiological changes of cellular function, size and function of organs are essential for the decision of therapeutic options. Among the various chronic conditions seen in elderly people, we have focuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Older patients use significantly greater health care resources than younger patients, especially during hospitalization [ 3 , 4 , 5 ]. In the setting of increasing longevity in different societies, the proportion of hospitalized older adults with cirrhosis, compared to those who are younger, continues to increase [ 6 , 7 , 8 ]. Aging adversely affects hepatic function, responses to injury, and complications of cirrhosis [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Older patients use significantly greater health care resources than younger patients, especially during hospitalization [ 3 , 4 , 5 ]. In the setting of increasing longevity in different societies, the proportion of hospitalized older adults with cirrhosis, compared to those who are younger, continues to increase [ 6 , 7 , 8 ]. Aging adversely affects hepatic function, responses to injury, and complications of cirrhosis [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…This finding can be explained by the lower life expectancy, higher comorbidities, and expensive cirrhosis treatments. 50,51 More ever their low level of awareness may also delay the diagnosis and treatment. 39 Strengths and limitations.…”
Section: Discussionmentioning
confidence: 99%
“…In almost all societies, the health system cares more about people with lower age and high physical condition. This finding can be explained by the lower life expectancy, higher comorbidities, and expensive cirrhosis treatments 50,51 . More ever their low level of awareness may also delay the diagnosis and treatment 39 …”
Section: Discussionmentioning
confidence: 99%
“…In age and gender subgroup analyses, older patients and men with DM had significantly greater evidence of HE (p-value 0.02 and 0.03, respectively). Multivariate analysis showed that DM (p-value 0.03) and older age (p-value 0.006) were independently related to HE [ 12 ], as increased transient time secondary to autonomic dysfunction in diabetes that often occurs in elderly patients may lead to HE [ 13 ], whereas the association of gender was non-significant [ 12 ].…”
Section: Discussionmentioning
confidence: 99%